2009
DOI: 10.1111/j.1750-3841.2008.01035.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Meat Binding Formulations on Thermal Inactivation of Escherichia coli O157:H7 Internalized in Beef

Abstract: This study evaluated the effects of meat binding or restructuring formulations, including salt/phosphate, algin/calcium, ActivaRM, and Fibrimex, with or without 0.27% (wt/wt) lactic acid, on thermal inactivation of internalized Escherichia coli O157:H7 in ground beef, serving as a model system for restructured products. Ground beef batches (700 g; approximately 5% fat) were mechanically mixed with a 5-strain composite of E. coli O157:H7 (7 log CFU/g) and then with the restructuring formulations. Product portio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
3
13
1
Order By: Relevance
“…0.05) changes in bacterial populations were observed following overnight storage of samples at 4 C, regardless of the treatment or plating medium (Tables 2e4). Consistent with previous studies (Calicioglu, Sofos, Samelis, Kendall, & Smith, 2002;Mukherjee et al, 2008;Yoon, Calicioglu, Kendall, Smith, & Sofos, 2005;Yoon et al, 2009), overnight acidified marination at 4 C did not lead to dramatic reductions of E. coli O157:H7 populations in raw beef.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…0.05) changes in bacterial populations were observed following overnight storage of samples at 4 C, regardless of the treatment or plating medium (Tables 2e4). Consistent with previous studies (Calicioglu, Sofos, Samelis, Kendall, & Smith, 2002;Mukherjee et al, 2008;Yoon, Calicioglu, Kendall, Smith, & Sofos, 2005;Yoon et al, 2009), overnight acidified marination at 4 C did not lead to dramatic reductions of E. coli O157:H7 populations in raw beef.…”
Section: Resultssupporting
confidence: 92%
“…This finding is most likely due to the lowering of the pH of samples containing AA (Table 5), which sensitized the microbial cells to heat during cooking (Yoon et al, 2009). Mukherjee et al (2008) and Yoon et al (2009) also found enhanced destruction during cooking to the same final temperature, of E. coli O157:H7 internalized in AA-treated beef samples. In the latter studies, AA was tested alone, or in combination with one or two tenderizing/flavoring ingredients; specifically, NaCl (0.5%), NaCl þ calcium ascorbate (0.86%), or NaCl þ calcium chloride (0.23%).…”
Section: Resultsmentioning
confidence: 67%
See 3 more Smart Citations